Numerical characterization of solar radiation applied to a simplified five parameters diode model of a photovoltaic module in the city of Ngaoundere - Gildas Armel , Fouakeu-nanfack; Jacques , Bikai; Felix Junior , Ngouem; Ngasop , Ndjiya; Edoun, Marcel; Marcel , Edoun (International Journal of Engineering and Technology, 2024)
In this paper, another simple and accurate approach to reconstructing the characteristics of a photovoltaic (PV) array exposed to solar radia-tion has been presented. This approach uses a five-parameter diode model. The approach is based exclusively on the manufacturer's data (three-point method: short-circuit current, open-circuit voltage, maximum power point). To carry out this work, we first carried out a numer-ical characterization of local solar radiation in the city of Ngaoundere. We then established the mathematical equations describing a solar photovoltaic module, and ran a numerical simulation on Matlab Simulink under standard conditions. The electrical parameters of the photo-voltaic generator and its optimal electrical quantities (current, voltage and power) were analyzed as a function of meteorological variations (temperature, irradiance) and series resistance. The simulation results show that we can achieve a maximum solar irradiance of 1214.9W/m2 in the city of Ngaoundere at solar noon. It has been shown that increasing solar irradiance is one of the most productive factors in a PV module. It was also shown that increasing temperature and series resistance considerably reduces the performance of a solar photovoltaic module. This result has enabled us to confirm that these PV cells perform best in a cold, clear-sky environment.